2008
DOI: 10.1038/sj.bjc.6604452
|View full text |Cite
|
Sign up to set email alerts
|

DLEC1 and MLH1 promoter methylation are associated with poor prognosis in non-small cell lung carcinoma

Abstract: The significance of chromosome 3p gene alterations in lung cancer is poorly understood. This study set out to investigate promoter methylation in the deleted in lung and oesophageal cancer 1 (DLEC1), MLH1 and other 3p genes in 239 non-small cell lung carcinomas (NSCLC). DLEC1 was methylated in 38.7%, MLH1 in 35.7%, RARb in 51.7%, RASSF1A in 32.4% and BLU in 35.3% of tumours. Any two of the gene alterations were associated with each other except RARb. DLEC1 methylation was an independent marker of poor survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 31 publications
2
77
1
Order By: Relevance
“…The prognostic potential of our HPV16 methylation biomarker is consistent with what has been reported for certain host gene DNA methylation differences between pre/cancer cells and normal cells at other body sites (e.g., refs. [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic potential of our HPV16 methylation biomarker is consistent with what has been reported for certain host gene DNA methylation differences between pre/cancer cells and normal cells at other body sites (e.g., refs. [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of RASSF1A, PTEN, DAPK, p16, Wif-1, CXCL12, DLEC1, MLH1, H-cadherin, APC, RUNX3, H-cadherin, SPARC, and DAL-1 was significantly associated with poor prognosis in patients with surgically resected lung adenocarcinomas/ squamous cell carcinomas. 101,106,[108][109][110][111][112][113] In addition, methylation of 14-3-3 sigma in pretreatment serum DNA was found to be an independent prognostic factor for survival in patients with lung adenocarcinoma, squamous cell carcinoma, and large cell carcinoma who were treated with platinum-based chemotherapy. 114 Previous researchers have reported that methylation, in addition to occurring in tumor tissues, can also be detected in blood samples or in exfoliated material of the aero-digestive tract epithelium from lung cancer patients, such as the methylation of RASSF1A, 115,116 p16, H-cadherin, 117 MAGE A1, and MAGE B2.…”
Section: Methylationmentioning
confidence: 99%
“…in various types of human cancers, 14,[19][20][21][22][23] suggesting that their loss of activity has a contributory role in cancer development or progression. Long-range epigenetic silencing across the 3p22 region was strongly associated with the presence of the activating BRAF V600E mutation, consistent with previous findings for MLH1 alone.…”
mentioning
confidence: 99%